character Employment Techniques in Modern Iraqi Poetry (The Poetry of the Nineties as a Model) - Ali Abdel Rahim Karim ((Humanities, social and applied sciences) Misan Journal of Academic Studies, 2023)
Any poetic text includes a set of messages transmitted by the creator, and these messages do not communicate directly along the line, as they include a set of codes whose solution needs a reference for the recipient to decipher them, including the personality, which is one of the most important signs that bears many tasks in the motives of action and the completion of the effect. At the level of the poetic text, and by locating their locations, the minor signs that are determined by the major signs are revealed, how does the poet deal with the element of personality, with the modern poetic vision presented to him, of stylistic techniques (such as the mask and the mirror) that help him to contrast the constructive with the narrative mechanisms, especially that The openness of the modern poem to other genres led to an open constructive formation, which achieved a new constructive function that fits the nature of the literary genre employed in it.